THE PARAMETRIC REPRESENTATION OF THE SPACE b_α^2 OF HARMONIC FUNCTIONS - Petrosyan, A. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In the paper the parametric representation for Hilbert spaces b_α^2(B) of functions harmonic in the unit ball BR_n is obtained.